Integrated Management of rainwater for crop-livestock agroecosystems - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2011)
With mixed crop-livestock systems projected to remain the main providers of food (animal and plant) in the coming decades, opportunities exist for smallholders to participate and benefit from emerging crop and livestock markets in the Volta Basin. Given the economic, social and environmental vulnerability due to high water scar- city and variability in the basin, improvements in rainwa- ter management are needed for ensuring sustainable and equitable benefits.